Agglomerations and the rise of urban network externalities*. (March 2016) - Burger, Martijn J.; Meijers, Evert J.; Meijers, Evert; Burger, Martijn
Abstract: This paper introduces the theme of the special issue 'Agglomerations and the Rise of Urban Network Externalities'. Urban network externalities are defined as external economies from which firms and households can benefit by being located in agglomerations that are well embedded in networks that connect with other agglomerations. The contributions focus on the conceptualization of urban network externalities and their influence on urban performance. Finally, a research agenda is presented, that should focus on multiplexity and heterogeneity in networks and their impacts; interrelations between agglomerations and networks and their dynamic and place‐based nature; and, the policy implications of urban network externalities.